Molecular archaeology of human cognitive traits - Kaczanowska, Joanna; Ganglberger, Florian; Chernomor, Olga; Kargl, Dominic; Galik, Bence; Heß, Andreas; Moodley, Yoshan; von Haeseler, Arndt; Bühler, Katja; Haubensak, Wulf (Cell Reports, 2022)
The brains and minds of our human ancestors remain inaccessible for experimental exploration. Therefore, we reconstructed human cognitive evolution by projecting nonsynonymous/synonymous rate ratios (ω values) in mammalian phylogeny onto the anatomically modern human (AMH) brain. This atlas retraces human neurogenetic selection and allows imputation of ancestral evolution in task-related functional networks (FNs). Adaptive evolution (high ω values) is associated with excitatory neurons and synaptic function. It shifted from FNs for motor control in anthropoid ancestry (60–41 mya) to attention in ancient hominoids (26–19 mya) and hominids (19–7.4 mya). Selection in FNs for language emerged with an early hominin ancestor (7.4–1.7 mya) and was later accompanied by adaptive evolution in FNs for strategic thinking during recent (0.8 mya–present) speciation of AMHs. This pattern mirrors increasingly complex cognitive demands and suggests that co-selection for language alongside strategic thinking may have separated AMHs from their archaic Denisovan and Neanderthal relatives.
CRIS-Team Scopus Importer:2022-09-09
Keywords: archaic brains; attention; computational neuroanatomy; CP: Neuroscience; Denisovan; evolutionary genetics; human cognition; language; Neanderthal; neurogenetic evolution; strategic thinking